2017
DOI: 10.1039/c7mt00123a
|View full text |Cite
|
Sign up to set email alerts
|

Chronic exposure to inorganic mercury induces biochemical and morphological changes in the salivary glands of rats

Abstract: Mercury exposure is considered to be a public health problem due to the generation of toxic effects on human health as a result of environmental and occupational conditions. The inorganic form of mercury (HgCl) can cause several biological changes in cells and tissues through its cumulative toxic potential, but little has been experimentally proven about the effects of inorganic mercury on salivary glands, an important modulator organ of oral health. This study analyzes the effects of prolonged low dose exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Previous reports have shown that major salivary glands are susceptible to metalinduced toxicity in models of exposure to lead [21], inorganic mercury [16], and methylmercury [17][18][19]. The last model also induces several proteomic damages, in the parotid and submandibular glands, especially changes in proteins related to cytoskeleton and energy metabolism pathways [17].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous reports have shown that major salivary glands are susceptible to metalinduced toxicity in models of exposure to lead [21], inorganic mercury [16], and methylmercury [17][18][19]. The last model also induces several proteomic damages, in the parotid and submandibular glands, especially changes in proteins related to cytoskeleton and energy metabolism pathways [17].…”
Section: Discussionmentioning
confidence: 98%
“…Our group has performed several studies regarding the effects of metals on the salivary glands in animal models, showing that those elements are capable of trigger tissue and redox impairments that affect the animals' stomatognathic system [16][17][18][19][20][21][22]. Other studies have also revealed damage to those organs after Al exposure [27,28], but to the best of our knowledge, this is the first study that used a proteomic approach to investigate the effects of exposure to a translational dose of Al over salivary glands.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although inorganic species have unfavorable physical-chemical characteristics to biomagnify and bioaccumulate, the presence of IHg in contaminated fish commercially available and consumed by humans was already evidenced [ 6 ]. In the past few years, our group has shown that several other organs are susceptible to IHg toxicity, such as blood [ 16 ], salivary glands [ 23 ], and the central nervous structures such as the hippocampus, motor cortex, and spinal cord [ 17 , 18 , 19 , 20 , 21 ] after the exposure to 0.375 mg/kg per day of HgCl 2 . Then, despite all the toxicokinetic features, the long-term exposure to IHg increased the levels of total mercury in cerebellar parenchyma of adult rats about 4-fold higher than non-exposed animals significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Each sample of hippocampus and cerebellum were weighted (weighting 0.5 g maximum), which consists in wet digestion of samples through homogenizing a wet sample; further, 1 mL of distilled water, 2 mL of nitric acid-perchloric acid 1:1 (v:v) (HNO 3 -HClO 4 ), and 5 mL of sulfuric acid (H 2 SO 4 ) were sequentially added, which were maintained on a heat plate (200–230 °C) for 30 min. All procedures were based on protocol, following previously published studies by our research group [21] , [22] , [32] , [33] , [43] , with a limit of detection of values until 0.001 mg/kg Hg. The results were expressed in mg/kg of total Hg levels.…”
Section: Methodsmentioning
confidence: 99%